2020
DOI: 10.1111/jep.13354
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of pressure ulcers in hospitalized adult patients in Bursa, Turkey: A multicentre, point prevalence study

Abstract: Rationale, aims, and objectives: Pressure ulcers (PUs), which are preventable complications, increase the cost of health care and the risk of prolonged hospital stay, as well as morbidity and mortality. In this study, we aimed to describe the prevalence, clinical features, and risk factors for PUs among hospitalized patients. Method: This study was cross-sectional and conducted over a single day in all the care units. Data were recorded on a patient observation form that included demographic data, diagnosis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 29 publications
(95 reference statements)
4
18
0
1
Order By: Relevance
“…These results agreement with the study performed by (Cox et al, 2020) who detected that sex, age, and Braden Scale score on admission were all predictive of pressure injury. Also, supported with the study by (Sayan et al, 2020) who showed that occurrence of PU is associated with increasing age and severity of patient clinical status, as predicted by the Braden Scale score and increase the length of stay at the hospital.…”
Section: Statistical Designsupporting
confidence: 79%
“…These results agreement with the study performed by (Cox et al, 2020) who detected that sex, age, and Braden Scale score on admission were all predictive of pressure injury. Also, supported with the study by (Sayan et al, 2020) who showed that occurrence of PU is associated with increasing age and severity of patient clinical status, as predicted by the Braden Scale score and increase the length of stay at the hospital.…”
Section: Statistical Designsupporting
confidence: 79%
“…Gender was not a significant PI risk factor in this study. Previously gender has been either identified or not as a PI risk factor 5,15‐17,26,30 …”
Section: Discussionmentioning
confidence: 99%
“… 5 Some studies have shown only low BMIs to be a significant risk for PI. 26 , 28 Additionally, recent studies have identified comorbidities in patients with a PI. More often found comorbidity was diabetes 15 , 16 , 25 , 26 , 28 , 31 and cardiovascular disease or congestive heart failure.…”
Section: Introductionmentioning
confidence: 99%
“…Bed sore incidence is always on rise in any ICU 7 . After the implementation of SOPs based management and an increase in nursing staff the incidence of bedsore also showed a detrimental pattern from 35 % to 19%.…”
Section: Age Incidencementioning
confidence: 99%